Analysis on Microstructural Features and Tensile Properties of Acrylic-Coated Banana-Polyester Synthetic Leather - Mohd Faisal, Nurathirah Nadiah; Shaari, Muhammad Farid (Progress in Engineering Application and Technology, 2025)
The increasing demand for sustainable and eco-friendly materials has led to a growing interest in synthetic leather alternatives. This study explores the use of banana fiber combined with polyester (BF-PE) as a sustainable alternative, bonded and coated with eco-friendly acrylic binders. The research addresses the challenge of improving adhesion and tensile properties between banana fibers and acrylic binders to enhance durability and mechanical performance. Nonwoven BF-PE fabric was coated using acrylic solutions with two dilution ratios: 50% acrylic and 50% water (A50W50) and 80% acrylic and 20% water (A80W20). Samples were subjected to compression pressures of 2 kPa, 4 kPa, and 6 kPa to study the effects of binder concentration and pressure on mechanical and microstructural properties. Results showed that the A50W50 sample at 4 kPa compression exhibited the most balanced characteristics for synthetic leather applications, with a tensile strength of 1.063 MPa and a Young’s Modulus of 21.817 MPa. This combination provided flexibility, strength, and a smooth surface finish. The findings demonstrate that acrylic-coated banana-polyester fabrics are promising sustainable alternatives to conventional synthetic leathers. They offer environmental and economic benefits, aligning with global efforts to reduce dependence on non-renewable resources and promote sustainable material development.